Endocanabinoide no condicionamento contextual a drogas de abuso: uma revisão de literatura - Aline de Castro Santos (2020)
Endocannabinoids are lipid mediators that interact with cannabinoid receptors, that recognize Δ9 tetrahydrocannabinol, the main psychoactive component of Cannabis sativa. Drugs of abuse produce similar changes in specific brain pathways, including reward circuits. The endocannabinoid system modulates these pathways and has been studied as a crucial component of this circuit underlying drug effects. A model frequently used for the study of rewarding effects of drugs is the conditioned place preference (CPP). This review presents data and discusses the involvement of the endocannabinoid system in CPP induced by drugs such as cocaine, alcohol, opioids, nicotine and amphetamine. The endocannabinoid system is involved in the effects of drugs of abuse, in which CB1 receptor antagonists and CB2 receptors agonists reduce the rewardign effects induced by certain drugs.